Increased Abdominal Adiposity in Adolescents and Young Adults With Classical Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency - Kim, Mimi S.; Ryabets-Lienhard, Anna; Dao-Tran, Anh; Mittelman, Steven D.; Gilsanz, Vicente; Schrager, Sheree M.; Geffner, Mitchell E. (The journal of clinical endocrinology and metabolism, 2015)
Context:Childhood obesity rates in congenital adrenal hyperplasia (CAH) exceed the high rates seen in normal children, potentially increasing their risk of cardiovascular disease (CVD). Abdominal adiposity, in particular visceral adipose tissue (VAT), is strongly associated with metabolic syndrome and CVD. However, it remains unknown whether VAT is increased in CAH.Objective:The objective of the study was to determine whether adolescents and young adults with classical CAH have more VAT and sc adipose tissue (SAT) than matched controls and whether VAT and SAT are associated with biomarkers of metabolic syndrome, inflammation, and hyperandrogenism in CAH.Design/Setting:This was a cross-sectional study at a tertiary center.Participants:CAH subjects (n = 28; 15.6 ± 3.2 y; 15 females) were matched for age, sex, ethnicity, and body mass index to healthy controls (n = 28; 16.7 ± 2.3 y; 15 females).Main Outcome Measures:VAT and SAT, using computed tomography imaging and serum biomarkers associated with CVD risk, were measured. Data are reported as mean ± SD.Results:Both VAT (43.8 ± 45.5 cm2) and SAT (288.1 ± 206.5 cm2) were higher in CAH subjects than controls (VAT 26.4 ± 29.6 cm2 and SAT 226.3 ± 157.5 cm2; both P < .001). The VAT to SAT ratio was also higher in CAH subjects (0.15 ± 0.07) than controls (0.12 ± 0.06; P < .05). Within CAH, measures of obesity (waist to height ratio, fat mass) and inflammation (plasminogen activator inhibitor-1, high-sensitivity C-reactive protein, leptin) correlated strongly with VAT and SAT. In addition, homeostasis model assessment of insulin resistance, and low-density lipoprotein correlated with abdominal adiposity. There were no sex differences for VAT or SAT in CAH subjects.Conclusions:CAH adolescents and young adults have increased abdominal adiposity, with a higher proportion of proinflammatory VAT than SAT. An improved understanding of the mechanism of obesity in CAH may lead to targeted prevention and therapeutics in this high-risk population.